EFFECT OF E-WOM AND PERCEIVED VALUE ON PURCHASE DECISIONS - Zulkarnain, Muhammad (IHTIYATH : Jurnal Manajemen Keuangan Syariah, 2021)
This study was conducted with the aim of analyzing the effect of e-wom and perceived value on purchasing decisions at the Shopee online store for consumers in Langsa City. The study used primary data sourced from research questionnaires. The study used a sample of 96 people with data analysis methods using multiple linear regression equations, t test, F test and R2 test. The results of the study show that e-wom and perceived value have a positive and significant effect on purchasing decisions made by consumers at the Shopee online store. Keywords: e-wom; value perception, purchase decision, Shopee